Pengaruh Aplikasi AI dalam Pola Belajar Murid SD/MI di Indonesia - Sekar Harum Pratiwi; Nurul Fakhrin; Guesa Maiwinda (Journal of Social, Educational and Religious Studies, 2025)
This study aims to analyze the impact of the use of artificial intelligence (AI)-based applications on the learning patterns of elementary school/Islamic elementary school (SD/MI) students in Indonesia. The research background stems from the need for more adaptive, interactive learning methods that align with developments in educational technology in the digital era. AI applications are believed to provide personalized learning experiences and assist teachers in monitoring student progress more effectively. The research method used a literature review, collecting data through reading materials, libraries, journals, and related articles. The main focus of the study was to examine how AI applications affect student motivation, conceptual understanding, and interaction during the learning process. The analysis was conducted by comparing the learning patterns of students using AI applications with those using conventional learning methods. The results showed that AI applications had a positive impact on increasing learning motivation, material understanding, and personalized learning. Students were more active and enthusiastic in participating in learning activities because the material was presented interactively and tailored to individual abilities. Teachers also benefited from analytical data that assisted in designing more targeted learning strategies.